Moisture content effect in the relationship between apparent electrical conductivity and soil attributes - Costa, Marcelo Marques; Queiroz, Daniel Marçal de; Pinto, Francisco de Assis de Carvalho; Reis, Elton Fialho dos; Santos, Nerilson Terra (Acta Scientiarum. Agronomy, 2014)
To map the spatial variability of a field to define the variable rate application, an intensive sampling of the soil-plant system is necessary. The apparent soil electrical conductivity (ECa) has been used for soil mapping because it correlates well with soil attributes, allows for dense sampling and can be obtained at low cost. However, ECa is influenced by soil moisture content, and the variability of this attribute can reduce the reliability of the ECa maps to explain the physical and chemical soil attributes. The objective of this study was to identify conditions that maximize the correlations between the ECa and the soil attributes. The results show that the mean soil moisture content of soil sampled on different dates was correlated with the mean of the ECa. The ideal time for measuring ECa occurred when the mean moisture content of the soil was higher. In this condition, the coefficient of variation for the soil moisture content was lower, there was no correlation between ECa and soil moisture content, and ECa was more correlated with other soil attributes evaluated in this work.